Spirituality: Do teachers and students hold the same opinion? - Banin, Luciana Burgugi; Suzart, Nadielle Brandani; Banin, Vanessa Burgugi [UNESP]; Mariotti, Luis Langoni; Guimarães, Fernando Garcia; Lucchetti, Giancarlo (Wiley, 2013)
Background:  Few studies have investigated potential differences between the opinions of educators and undergraduates regarding spirituality in patient care. Understanding these differences, could lead to better strategies for educational proposes. Purpose:  To compare the opinions of medical teachers (MTs) and medical students (MSs) regarding spirituality training in a Brazilian medical school. Methods:  A cross-sectional study was conducted. MTs and MSs filled out a questionnaire containing the Duke Religion Index, and questions regarding spirituality in clinical practice and at medical school. A comparison between early-curriculum MSs, late curriculum MSs and MTs was carried out. Chi-square (categorical) and Mann-Whitney (continuous/ordinal) tests were used. Results:  A total of 475 MSs and 44 MTs were evaluated. Results showed that MSs did not address spirituality as frequently as MTs (p<0.001), and that most participants did not feel prepared to address this issue, and believe that Brazilian medical schools are not giving all the required information in this field. Nevertheless, they believe MSs should be prepared to discuss these issues. Late-curriculum MSs believed that spirituality plays a more positive role in patient health (p=0.027), and were more prone to address this issue than early-curriculum MSs (p=0.023). Conclusion:  These findings revealed some of the challenges faced by spirituality medical training in Brazil, and differences between MTs and MSs regarding this issue. Further studies are needed to replicate these findings in other countries. © Blackwell Publishing Ltd 2013.
Keywords: adult; Brazil; cross-sectional study; curriculum; female; health personnel attitude; human; male; medical education; medical school; medical student; middle aged; organization and management; psychological aspect; religion; time; Adult; Attitude of Health Personnel; Cross-Sectional Studies; Curriculum; Education, Medical, Undergraduate; Faculty, Medical; Female; Humans; Male; Middle Aged; Religion and Medicine; Spirituality; Students, Medical; Time Factors